Unilateral synchronous papillary renal neoplasm with reverse polarity and clear cell renal cell carcinoma: a case report with KRAS and PIK3CA mutations - Hyun Jung Lee; Dong Hoon Shin; Joon Young Park; So Young Kim; Chung Su Hwang; Jung Hee Lee; Jee Yeon Kim; Mee Young Sol; Jong Kil Nam (BMC, 2020)
Abstract Background The presence of histologically different neoplasms in the same organ is rare in pathologic practice. We report the first case of synchronous clear cell renal cell carcinoma (clear cell RCC) and papillary renal neoplasm with reverse polarity (PRNRP) with comprehensive immunohistochemical and molecular characterization using next-generation sequencing (NGS). Case presentation A 61-year-old man was incidentally found to have a left renal mass on imaging studies performed for workup of left back pain and urine color change for 1 week. A laparoscopic left radical nephrectomy was performed. Gross examination showed lobulated masses measuring 5.6 × 4.0 × 3.3 cm in the upper to mid pole and 1.1 × 1.0 × 1.0 cm in the lower pole. Microscopic findings revealed these to be two different separate masses of clear cell renal cell carcinoma and papillary renal neoplasm with reverse polarity. NGS analyses revealed KRAS gene mutation (c.35G > T/p.G12V in exon 2) in the papillary renal neoplasm with reverse polarity, with PIK3CA gene mutation restricted to the clear cell renal cell carcinoma (c.1624G > A/p.E542K in exon 10). Conclusions We report here an extraordinarily rare case of synchronous renal tumors of papillary renal neoplasm with reverse polarity and clear cell renal cell carcinoma. We identified simultaneous KRAS and PIK3CA mutations in two different renal masses in the same kidney for the first time. New pathologic assessment with comparative molecular analysis of mutational profiles may be helpful for tumor studies.